Efektivitas Model Problem Based Learning Berbantuan GeoGebra Classroom untuk Meningkatan Kemampuan Literasi Matematis Siswa Tunarungu - Nilam Arum Setyaningsih; Sugiman Sugiman (Hayati : Jurnal Pendidikan, 2025)
This study aims to determine the effectiveness of the implementation of the GeoGebra Classroom-assisted Problem Based Learning model to improve the mathematical literacy skills of deaf students in geometry material. The study also describes the mathematical literacy skills of deaf students by implementing the GeoGebra Classroom-assisted Problem Based Learning model. The method used is mixed methods, which is a combined approach between quantitative and qualitative. The research conducted applies a quantitative approach with the Single Subject Research (SSR) method with an A-B-A design, namely baseline-1 (A1), intervention, and baseline-2 (A2) phase which is continued with a qualitative approach with a qualitative descriptive method. The subjects of the study were five deaf students in class X of SLBN Semarang. Data collection techniques using the form of observation, interviews, questionnaires, and tests. Data analyzed using descriptive statistics, data reduction, data presentation, data interpretation, and drawing conclusions. The results of the study indicate that: 1) the GeoGebra Classroom-assisted Problem Based Learning model is effective in improving the mathematical literacy skills of all subjects. Cognitively, there was an increase in the value of the five subjects respectively by 24, 11, 24, 23.5, and 26 points. The affective aspect also showed an increase in the dimensions of curiosity, accuracy, responsibility, never giving up, enthusiasm for learning, self-confidence, and interest in learning. The psychomotor aspect also showed an increase in all dimensions 2) the responses of the five research subjects were very positive by 90.90%, 95.45%, 86.36%, 97.72%, and 88.63%.